Analysis of the practical measurement of electrical echo parameters in mobile communications - Ovcharenko, D. R. (ХНУРЕ, 2024)
The results of practical measurements of echo signal delays during calls in the networks of mobile operators in Ukraine are presented. It is shown that with the help of electrical echo, facts of call redirection to the network of another operator can be detected, since the echo delay increases. It has been established that the use of a roaming SIM card will not allow simulating a stay in another country if it is registered in the network of the national telecom operator. The use of IP telephony when calling to mobile networks is also clearly determined by the echo delay.
Keywords: mobile communications